PELATIHAN PEMBUATAN ECOBRICK SAMPAH PLASTIK SEBAGAI SALAH SATU UPAYA PEMBERSIHAN PERAIRAN SUNGAI CITARUM - Patanda, Mercy; Dhewantara, Yudha Lestira (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2023)
Ecobrick is waste management method in which plastic bottles are filled withinorganic waste until they are solid and compact, aiming to reduce plasticwaste and recycle it into something useful. This activity was carried out in theCitarum River Basin, Karawang Regency, West Java Province, from October2018 January 2019, as part of Citarum Harum program. The programincluded Ecobrick creation training to support river water cleaning efforts.Observations were conducted through field surveys, interviews, and FGD,with evaluations using questionnaires before and after socialization. Theresults showed that while participants not directly dispose of waste into theriver, they still accumulated waste in vacant land around their homes. Thesocialization increased participants' knowledge of the benefits of Ecobricks forenvironmental cleanliness and encouraged them to be more active in creatingEcobricks and maintaining cleanliness. The program also raised awarenessabout the importance of sustainable and eco-friendly waste management.